2007
DOI: 10.1017/s031716710000682x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress after Subarachnoid Hemorrhage in gp91phox Knockout Mice

Abstract: 356Spontaneous subarachnoid hemorrhage (SAH) represents 5-7% of all strokes, 1,2 and SAH-related mortality reaches 50%. [3][4][5] Acute cerebral ischemia and subsequent injury are major causes of morbidity after SAH. 3,6 Several studies, including investigations in superoxide dismutase (SOD) transgenic mice, showed that superoxide and other reactive oxygen species (ROS) largely contribute to the early brain injury after SAH. [7][8][9][10][11] NADPH oxidase has been primarily described as responsible for supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…At this point, the impossibility of controlling the degree of SAH has to be mentioned again as the most crucial disadvantage of the cWp model, as already discussed in the literature [4,9]. Advantages and disadvantages of the cWp model com-pared with other models have been discussed in detail else-where [1,4,10,19]. In brief, the cWp model is technically (surgically) the most challenging model.…”
Section: Discussionmentioning
confidence: 96%
“…At this point, the impossibility of controlling the degree of SAH has to be mentioned again as the most crucial disadvantage of the cWp model, as already discussed in the literature [4,9]. Advantages and disadvantages of the cWp model com-pared with other models have been discussed in detail else-where [1,4,10,19]. In brief, the cWp model is technically (surgically) the most challenging model.…”
Section: Discussionmentioning
confidence: 96%
“…availability, size, or available standardized models, these species have, in contrast to mice, the inherent disadvantage of not being amenable to genetic manipulation. Therefore several groups developed murine SAH models by directly injecting blood into the cisterna magna (Lin et al, 2003), dissecting an intracisternal vein (Altay et al, 2009), or perforating an artery at the skull base by introducing a filament into the cerebral circulation through an extra-cranial approach (Kamii et al, 1999;Sozen et al, 2009;Ishikawa et al, 2009;Liu et al, 2007;McGirt et al, 2002a,b;Parra et al, 2002;Saito et al, 2001;Gao et al, 2006). The cisterna magna injection model and the venous dissection model can be performed quickly, are highly reproducible due to the controlled application of the blood, result in an acute increase of ICP and subsequent decrease of CBF, and lead the development of brain edema and intracranial hypertension as also observed in man (Broderick et al, 1994;Claassen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…So far several research groups studied SAH in mice either by perforating the Circle of Willis at the skull base using an intraluminal filament inserted through the external carotid artery (Kamii et al, 1999;Sozen et al, 2009;Ishikawa et al, 2009;Liu et al, 2007;McGirt et al, 2002a;Parra et al, 2002;Saito et al, 2001;Gao et McGirt et al, 2002b), by directly injecting blood into the cisterna magna (Lin et al, 2003), or by perforating an intracisternal vein (Altay et al, 2009). Since perforation of an intracerebral vessel by a filament resembles aneurysmal hemorrhage closer than intraventricular injection of blood, Circulus of Willis perforation (CWp) became the most widely used SAH model in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of oxidative stress in the development of SAH was suggested by demonstrating the presence of increased protein and lipid peroxidation in the brain and cerebrospinal fluid (Liu et al 2007;Clark et al 2008). Previous results demonstrated that hemolysate has been shown to induce oxidative stress directly and indirectly (Yoshida et al 1994;Matz et al 2000).…”
Section: Introductionmentioning
confidence: 99%